The Effect Of The Combination Of Concentration And Spraying Time Bioliquid Organic Fertilizer For Growth And Yield Sweet Corn Plant (Zea mays Var. saccharata sturt) Baruna Varieties - Wijaya Wijaya; Achmad Faqih; Rafi Arya Pratama; Yusri Amirudin; Fierda Haadiytianingrum; Galih Mulyadi Firdaus (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
This study aims to determine the effect of the combination of concentration and time of spraying bioliquid organic fertilizer on the growth and yield of sweet corn plants (Zea mays Var. saccharata Sturt) Baruna variety. The research was conducted in Tegalsari Village, Plered District, Cirebon Regency from January to May 2023. The experimental method used was using the experimental method with Group Random Design (RAK), consisting of 7 treatment combinations and repeated 4 times. Data analysis was carried out using fingerprints and further tests with the Duncan Multiple Distance Test at the level of 5%. After that, a Correlation Test was carried out with Product Moment t Test analysis between the growth components and the yield of sweet corn plants. The results showed a real influence between the concentration and time of spraying bioliquid organic fertilizer on plant height, number of leaves aged 60 HST, stem diameter, length of husked cob, diameter of husked cob, weight of cob per plant, and weight of husked cob per plot. The concentration of liquid organic fertilizer 5 ml/1 liter of water and spraying time of 14, 28, 42 HST showed the best effect on the weight of cob per plot resulting in production of 15.60 kg/plot or equivalent to 17.33 tons/ha.